2001
DOI: 10.1002/mrm.1290
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic patterns of USPIO enhancement can be observed in macrophages after ischemic brain damage

Abstract: Cells of the mononuclear phagocytotic system (MPS) are often found near to or within ischemic tissue and can potentially aggravate cellular damage. Hence, visualization of those cells would allow demarcation of putatively affected from intact tissue. Experimental MRI studies have shown that ultrasmall particles of dextran-coated iron oxide (USPIO) are internalized into cells of the MPS. To test if this cell tagging method may be also applied to cerebral infarction, USPIOs were administered to Fisher rats 5.5 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
3
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(101 citation statements)
references
References 19 publications
4
93
3
1
Order By: Relevance
“…Both ED and surge-type morning BP hypertensives are known to be at increased risk for vascular events (1, 2). PMNs have not been clearly identified as contributing to brain damage (14,15), but MNCs have been found in damaged brain tissues (19), which is consistent with our previous findings that ROS formation by PMNs and MNCs are differently regulated; ROS formation by PMNs is related with BP (20) and hemoglobin A1C, but not with blood glucose or CRP (9). ROS formation by MNCs is related to CRP (9).…”
Section: Discussionsupporting
confidence: 80%
“…Both ED and surge-type morning BP hypertensives are known to be at increased risk for vascular events (1, 2). PMNs have not been clearly identified as contributing to brain damage (14,15), but MNCs have been found in damaged brain tissues (19), which is consistent with our previous findings that ROS formation by PMNs and MNCs are differently regulated; ROS formation by PMNs is related with BP (20) and hemoglobin A1C, but not with blood glucose or CRP (9). ROS formation by MNCs is related to CRP (9).…”
Section: Discussionsupporting
confidence: 80%
“…Post-USPIO T2 values were recorded at day 3, 10 and 38 following TAM. The elimination half-life of the USPIO used is approximately 5 h (Dousset et al, 1999b) and the time, during which USPIO-labeled macrophages remain visible in MR images, is of the order of 2-3 days post-injection (Rausch et al, 2001). With an interval of 7 days between injections, the MR signal of subsequent measurements was not or only minimally affected by USPIOs administered during the previous imaging session.…”
Section: Methodsmentioning
confidence: 99%
“…In small animal models of MS (experimental autoimmune encephalomyelitis (EAE)), SPIO can be used to image macrophage activity [177] and infiltration [178], lymphocyte infiltration (CD3 + cells [179]) and the labeling of T-cells [180]. Also in the case of heart attack, numerous studies show that SPIO can image the accompanying neuroinflammation or the macrophage activity [181] and macrophage migration [182] similarly to the changes in MS. Moreover, it was able to be shown that early stages of post-radiogenic brain damage can be imaged via targeted SPIO-AB against ICAM-1 [183].…”
Section: Imaging Of Multiple Sclerosis (Ms) and Neurodegenerationmentioning
confidence: 99%